ANALISIS PENGARUH CASH CONVERTION CYCLE, INVESTMENT OPPORTUNITY SET, LEVERAGE, FIRM SIZE, DAN LIQUIDITY TERHADAP CASH HOLDING - Annisa Nurul Utmi; Zahara Zahara; Yossi Septriani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Cash is an important asset because cash is internal funding in a company. Companies must have a strategy for managing cash to prevent bad possibilities from occurring, such as crises in the future. One aspect of cash management used is cash holding. Cash holding refers to a company's decision to maintain a certain amount of cash or cash equivalents on their balance sheet, to meet short-term obligations, manage uncertainty, or to finance investments that may arise. This research aims to examine the influence of the cash conversion cycle, investment opportunity set, leverage, firm size and liquidity on cash holding. The data used in this research is secondary data obtained from the company's annual financial reports. This research focuses on companies operating in the retail sector that are listed on the Indonesia Stock Exchange for the period 2021 to 2023. The sampling technique uses a purposive sampling method so that the amount of data processed in this research is 104 data samples. To test the research hypothesis, multiple linear regression analysis was used using SPSS version 20. The research results show that investment opportunity set, leverage and liquidity have a positive influence on cash holding. Meanwhile, cash conversion cycle and firm size have no influence on cash holding. In future research, it is hoped that the research sample can be expanded by increasing the number of research periods. Future researchers can add other variables that can influence cash holding such as cash flow, cash flow variability, net working capital, sales growth, dividend payments and profitability.